Advanced practice and leadership in radiology nursing - Bowen, Michael; Butler, Shawna M.; Collinson, Randi L.; Dennis, Vangie; Dixon, Adrienne N.; Gross, Kathleen A. (Switzerland : Springer, 2020)
Endorsed by the Association of Radiologic and Imaging Nursing (ARIN), this first of a kind comprehensive radiology nursing textbook fills a gap by addressing important subjects for patient care and professional issues, as well as, future possibilities affecting nursing practice. It serves as a resource to related nursing specialties, e.g. critical care, emergency or peri-anesthesia, and to radiologic technologists and physician assistants. The book could be used as one resource for studying for radiologic nursing certification. The textbook is subdivided into five sections that address advanced practice and leadership roles, clinical patient care topics, safety topics, including legal considerations, e.g. infection prevention and equipment. It includes a section with topics impacting the patient experience and a section on professional topics, e.g. cybersecurity, social media, research/outcomes, interprofessional collaboration, workplace violence and current trends in imaging. The authors include advanced practice providers, radiology nurse managers, educators, physicians, a physicist, a dentist, attorneys, a child life specialist, administrators and a social worker. Radiology diagnostic examinations and therapeutic procedures have become a more prominent part of patient care due to advances in technology and the ability of radiology to provide services that were traditionally done in surgery or not done because of limited knowledge. Many procedures are facilitated by the radiology nurse from initial consult to transfer to a hospital unit or discharge and follow-up. Nurses assess, monitor, administer sedation/other medications and respond to emergencies. They serve as educators, researchers, and resource personnel to the radiology department and in many instances, to the entire facility. Radiology nurses are real leaders. In order to keep up-to-date on new developments, nurses...
La función de los autores fue determinada por el catalogador
Tambien disponible en formato EPUB
Keywords: ENFERMERÍA Y ENFERMERAS; RADIOLOGÍA MÉDICA; LIDERAZGO; ATENCIÓN AL ENFERMO